Advanced flavin catalysts elaborated with polymers. Issue 10 (October 2018) - Arakawa, Yukihiro; Minagawa, Keiji; Imada, Yasushi
Abstract A variety of biological redox reactions are mediated by flavoenzymes due to the unique redox activity of isoalloxazine ring systems, which are found in flavin cofactors. In the field of synthetic organic chemistry, the term "flavin" is generally used for not only isoalloxazines but also related molecules including their isomers and some analogs, and those having catalytic activity are calledflavin catalyst . Flavin catalysts are typically metal-free, and their catalytic activity can be readily accessed using mild terminal oxidants such as H2 O2 and O2 ; therefore, redox reactions with these compounds have great promise as alternatives to reactions with conventional metal catalysts for the sustainable production of important chemicals. We recently became interested in using polymers for the development of flavin catalysts, especially to improve their practicality and advance the field of catalysis. Here, we summarize our recent research on such flavin–polymer collaborations including the development of facile preparation methods for flavin catalysts using polymers, readily reusable polymer-supported flavin catalysts, and flavin–peptide–polymer hybrids that can catalyze the first flavoenzyme-mimetic aerobic oxygenation reactions. Flavin catalysts are typically metal-free, and their catalytic activity can be readily accessed using mild terminal oxidants such as H2 O2 and O2 ; therefore, redox reactions with these compounds have great promise as alternatives to reactions with conventional metal catalysts for the sustainable production of important chemicals. Herein, our recent research on flavin catalysts including the development of facile preparation methods for flavin catalysts using polymers, readily reusable polymer-supported flavin catalysts, and flavin-peptide-polymer hybrids that can catalyze the first flavoenzyme-mimetic aerobic oxygenation reactions is summarized.